Rancang Bangun Prototype Robot Pendeteksi Gas Metana Berbasis Mikrokontroler Arduino Untuk Eksplorasi Pertambangan - Ahnaf Faisal; Lovely Son (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
Accident which is occurred due to the harmful gas always found in the mining location. One example of harmful gas is the explosive methane gas. One of attempt to overcome this problem is by using a methane gas detector robot that can detect the gas early before the mining process is conducted. This kind of robot can be control autonomously from a place which is located far away from the mining area. Therefore, the mining workers can work safely. This research is aimed to design and manufacturing a mobile robot for detecting a methane gas in the mining area. The research is conducted step by step by making the mechanical components of robot, manufacturing the electronic circuits and programming the Arduino microcontroller using the Arduino IDE software. Mechanical design of the robot is targeted for operating the robot in the off-road environments. The main control center of the robot arm uses an Arduino UNO microcontroller. Robot control system has a methane gas detector to sense the methane gas. The command signal is applied autonomously by using Android based smart phone, which move the robot to the desired area. The signal sent by gas sensor MQ-04 will ring the buzzer and turn on the LED of the robot whenever the robot detects a methane gas. The experimental results shows that the robot can detect the methane gas and robot maneuvering can be conducted successfully.